Advancing Malaysian Practice-Based Education - Giridharan, Beena (Sense Publishers, 2013)
As an international language of communication, English in Malaysia is considered a critical language of commerce for Malaysia to maintain its competitive edge and for graduates to work and practise in a global context. It is a key to successful education for practice for these students. The official role of English in Malaysia is that of a second language (L2), with Malay as the first language and Tamil or Chinese as the third. The recent growth of the use of English in the “outer circle” as delineated by Kachru (1985) in countries such as Singapore and Malaysia has been extensive. In Malaysia the growth of English has been steady, and increased efforts have been made by English language researchers and teachers to encourage English proficiency among school students, particularly secondary school students.